2016
DOI: 10.1128/aem.00319-16
|View full text |Cite
|
Sign up to set email alerts
|

A Structurally Novel Chitinase from the Chitin-Degrading Hyperthermophilic Archaeon Thermococcus chitonophagus

Abstract: A structurally novel chitinase, Tc-ChiD, was identified from the hyperthermophilic archaeon Thermococcus chitonophagus, which can grow on chitin as the sole organic carbon source. The gene encoding Tc-ChiD contains regions corresponding to a signal sequence, two chitin-binding domains, and a putative catalytic domain. This catalytic domain shows no similarity with previously characterized chitinases but resembles an uncharacterized protein found in the mesophilic anaerobic bacterium Clostridium botulinum. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…The product profiles for Ss Chi18A and Ss Chi19A toward colloidal chitin were mainly G2 and G1, with visible amounts of G3 (Additional file 1: Fig. S2), a common feature for GH18 chitinases [22, 23]. In the product profiles of Ss Chi18B and Ss Chi18C, besides the major products G2 and G1, G4 and G5 were also accumulated, indicating that the functions of Ss Chi18B and Ss Chi18C may be different from that of Ss Chi18A.…”
Section: Resultsmentioning
confidence: 99%
“…The product profiles for Ss Chi18A and Ss Chi19A toward colloidal chitin were mainly G2 and G1, with visible amounts of G3 (Additional file 1: Fig. S2), a common feature for GH18 chitinases [22, 23]. In the product profiles of Ss Chi18B and Ss Chi18C, besides the major products G2 and G1, G4 and G5 were also accumulated, indicating that the functions of Ss Chi18B and Ss Chi18C may be different from that of Ss Chi18A.…”
Section: Resultsmentioning
confidence: 99%
“…chitonophagus is known to possess multiple chitinases (40)(41)(42). Recently, two groups of investigators have conducted genome analyses of this archaeon, and both predicted the presence of three chitinase genes (43,44). Reclassification of the organism to the genus Pyrococcus has also been proposed (species name Pyrococcus chitonophagus) (43).…”
Section: Discussionmentioning
confidence: 99%
“…Reclassification of the organism to the genus Pyrococcus has also been proposed (species name Pyrococcus chitonophagus) (43). Biochemical characterization of one of the T. chitonophagus chitinases, ChiD, has revealed that the enzyme is a structurally novel chitinase exhibiting exo-type activities and mainly releases (GlcNAc) 2 units from the reducing ends of chitin chains (44). As T. kodakarensis ChiA contains an endo-chitinase domain and an exochitinase domain that recognizes only the nonreducing ends of chitin chains, introduction of the ChiD gene into T. kodakarensis KC04ΔtM1 may further improve its chitin degradation capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Also, some archaea like Pyrococcus furiosus [4] or Thermococcus kodakarensis [5] can produce chitinase under hyperthermophilic conditions. Furthermore, just recently, a new family of chitinase from Thermococcus chitonophagus has been reported by Horiuchi et al [6] which contains two additional chitin-binding domains along with catalytic domains.…”
Section: Introductionmentioning
confidence: 99%